Postpartum depression: a case-control study. (2nd September 2021) - Silva, Racire Sampaio; Junior, Romildo Azevedo; Sampaio, Veronica Secchin; Rodrigues, Katrynni Oliveira; Fronza, Marcio
Abstract: Background: Postpartum depression (PPD) is a mild to severe mood disorder, starting at 6 weeks after birth and with an incidence of approximately 25% in Brazilian puerperae. Its occurrence induce significant aggravations to maternal and child health, however, its risk factors, although known, are little explored for the appropriate diagnosis. Purpose: To correlate PPD with anxiety, smoking, alcoholism, parity, type of birth, gestational and maternal age, identifying the possible risk factors that increase the probability of a puerpera developing a depressive episode. Materials and methods: A case-control study performed at the Alzir Bernardino Alves Infant and Maternity Hospital in the city of Vila Velha, Espirito Santo, Brazil. The sample consisted of 227 puerperae. The cutoff point for depression was defined as >10 points according to the Edinburgh Postnatal Depression Scale (EPDS), and cutoff points for anxiety were defined as <33 points for low anxiety, between 33 and 49 for moderate anxiety and >49 for high anxiety according to the State - Trait Anxiety Inventory (STAI-T). Results: 29.1% of the 227 interviewed puerperae presented PPD and were considered "cases", with the remaining being considered as "control". There was a positive correlation between PPD and anxiety. No significant correlation was observed for the other risk factors. Women with moderate anxiety presented 17.38 times more probability to develop depressive episodes, and puerperae with high anxiety presented 273 times more chance of developing PPD. Conclusions: Our results evidenced a high percentage of puerperae with PPD related to maternal anxiety, demonstrating the importance and the necessity of increasing care for women's mental health in the gestational and puerperal periods.